2021
DOI: 10.1089/pmr.2020.0095
|View full text |Cite
|
Sign up to set email alerts
|

Does Inpatient Palliative Care Facilitate Home-Based Palliative Care Postdischarge? A Retrospective Cohort Study

Abstract: Introduction: Evidence of the impact of inpatient palliative care on receiving home-based palliative care remains limited. Objectives: The objective of this study was to examine, at a population level, the association between receiving inpatient palliative care and home-based palliative care postdischarge. Design: We conducted a retrospective cohort study to examine the association between receiving inpatient palliative care and home-based palliative care within 21 days of hospital discharge among decedents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Finally, recent population-based studies have indicated that patients who received inpatient palliative care within six months prior to their death were more likely to access community palliative care after discharge than those who received no inpatient palliative care [55,56]. The receipt of community palliative care after hospital discharge has been shown to decrease readmissions and health care utilisation [57,58].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, recent population-based studies have indicated that patients who received inpatient palliative care within six months prior to their death were more likely to access community palliative care after discharge than those who received no inpatient palliative care [55,56]. The receipt of community palliative care after hospital discharge has been shown to decrease readmissions and health care utilisation [57,58].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…12 Inpatient palliative care improves the likelihood of receiving home-based palliative care and reduces the need for readmissions. 13 Importantly, early engagement with palliative care services is not mutually exclusive with the provision of life-prolonging treatment.…”
mentioning
confidence: 99%